2021
DOI: 10.1016/j.amsu.2021.102901
|View full text |Cite
|
Sign up to set email alerts
|

We can reduce negative paediatric appendicectomy rate: A cohort study

Abstract: Background Appendicitis accounts for the most frequent surgical emergencies in childhood. The guidance from the Royal College of Surgeons and poor post operative outcomes in surgical patients during the pandemic, it would be expected that only children who had clinical signs of appendicitis and were unwell, would have undergone surgery. Hence, the negative appendicectomy rate during the pandemic should have decreased. The aim of this retrospective study was to assess the rate of negat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…Comparable results were reported by Del Giorgio et al [50]. Some studies identified a significant increase in perforated case numbers during the pandemic despite similar durations of symptoms [25,26,45].…”
Section: Time To Hospital Admission Duration Of Symptoms and In-hospi...supporting
confidence: 63%
See 1 more Smart Citation
“…Comparable results were reported by Del Giorgio et al [50]. Some studies identified a significant increase in perforated case numbers during the pandemic despite similar durations of symptoms [25,26,45].…”
Section: Time To Hospital Admission Duration Of Symptoms and In-hospi...supporting
confidence: 63%
“…It is possible that during the pandemic, more effort was made to establish a correct diagnosis preoperatively. This could have been due to greater imaging use, more direct senior consultant involvement and a higher threshold for surgical exploration [43,45]. Cases that were diagnostically uncertain were more likely to be managed non-operatively during the pandemic, as recommended by guidelines [96,97].…”
Section: Delays In Primary Operative Management or Increased Time To ...mentioning
confidence: 99%
“…Of 528 title/abstract screened, 129 full-text articles were analyzed, 43 studies entered the qualitative analysis [ 1 11 , 13 , 14 , 22 – 51 ], and 36 papers were included in the meta-analysis [ 1 8 , 11 , 13 , 22 , 23 , 25 – 28 , 30 44 , 46 50 ] (32,704 pts, Fig. 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…All the 36 studies included in the meta-analysis were retrospective observational studies [ 1 8 , 11 , 13 , 22 , 23 , 25 – 28 , 30 44 , 46 50 ]. None of the papers provided sample size calculations.…”
Section: Discussionmentioning
confidence: 99%
“…The use of imaging modalities like ultrasound and computerized tomography have improved the diagnostic accuracy and reduced the negative appendectomy rate [34]. The use of ultrasound to diagnose acute appendicitis is useful as it involves any use of radiation, and it can be done in the emergency department.…”
Section: Imaging and Negative Appendectomymentioning
confidence: 99%